Um estudo matricial de projeção populacional baseada em faixas etárias no município de Acará/PA - SILVA, Wevertton da Silva e (2023)
The present work was performed to show new ways of generating and applying interdisciplinary information using Mathematics, specifically in the field of Linear Algebra. The applications of Linear Algebra in Population Biology show a promising branch of great importance and that requires more attention from professionals in both areas. The movements in the age structure of a population that are often accompanied by rural-urban migration were studied and are therefore a compelling case for the implications of fertility, mortality and migration patterns together. The general objective of this work was to analyze data on female population growth of these movements in the age structure in the municipality of Acará, State of Pará, using Leslie's matrix model to estimate the increase, or not, of the population in the future. Populus software were used to meet the overall objective. The model obtained allowed an analysis of long-term population properties, as well as a graphic comparison between the female population data provided by IBGE and DATASUS and those obtained after the study.